2013
DOI: 10.1111/psyg.12019
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological differentiation between Alzheimer's disease and dementia with Lewy bodies in a memory clinic

Abstract: Objective: The aim of this study was to identify a useful neuropsychological instrument for making a differential clinical diagnosis between Alzheimer's disease (AD) and dementia with Lewy bodies (DLB). Methods: We examined 402 AD and 38 DLB patients with neuropsychological tests that covered general cognition, frontal lobe cognitive function, non-verbal abstract reasoning, working memory and attention, and verbal memory. Discriminant analysis using a stepwise method was performed to identify the measures best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In addition, the AVLT 20‐min delayed recall was also a discriminator, but it had less area under the curve than the MES 5‐min delayed recall. Our findings confirmed previous reports of the discriminant value of delayed recall—including the delayed recall subscore of the MMSE, AVLT percentage retention, and Logical Memory subtests 1 and 2 of the Wechsler Memory Scale‐Revised—between these two types of dementias …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the AVLT 20‐min delayed recall was also a discriminator, but it had less area under the curve than the MES 5‐min delayed recall. Our findings confirmed previous reports of the discriminant value of delayed recall—including the delayed recall subscore of the MMSE, AVLT percentage retention, and Logical Memory subtests 1 and 2 of the Wechsler Memory Scale‐Revised—between these two types of dementias …”
Section: Discussionsupporting
confidence: 91%
“…Comparisons of language between these two types of dementias are still controversial. Several studies reported the differentiating values of neuropsychological measures between DLB and AD, but the neuropsychological tests, dementia severity of patients, and discriminant accuracy varied . Most of them used only Mini‐Mental State Examination (MMSE) subscores, rather than comprehensive neuropsychological assessment, to distinguish DLB from AD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlations found in the analysis may be affected by this variability. It has been reported that the patients with DLB have performed significantly worse than the patients with AD on RCPM (Kawai et al, 2013). RCPM has been useful to differentiate between AD and DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased occipital α activity showed correlation with worse brain functions related to attention/concentration (WMS-R-attention/concentration, Verbal Fluency Test for words), visuospatial discrimination (VPTA-shape discrimination scales), and global cognition (ADAS-J cog, CDR sum of boxes). Neuropsychological studies revealed that DLB patients have prominent functional deficits in attention, visual perception, working memory, and frontal executive function compared to AD [65-67]. The occipital dominant impairment observed in DLB patients could explain the deficits in visual attention and visual perception because visual information flows from the occipital cortex to higher cognitive areas such as the VAN and DAN [68].…”
Section: Discussionmentioning
confidence: 99%